Kitab Asmarakandi sebagai Sumber Belajar Pendidikan Islam Awal di Nusantara - Muhammad Nabil Fahmi; Muqowim Muqowim (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2021)
During the classical period, Islamic education in the Indonesian archipelago (Nusantara) could not be separated from the literature used. One of the earliest pieces of literature that have been used in the Nusantara since the 16th century AD is Asmarakandi book by Abū al-Laiṡ as-Samarqandī. This research aims to explain the significance and characteristics of the Asmakarakandi book related to its function as a learning resource and its implications for the implementation of early Islamic education in the Nusantara. This research is a literature review using the integration-interconnection scientific paradigm, namely the historical approach in Islamic studies. This research finds that the Asmarakandi book is a popular basic level of Islamic education learning resource used by Muslim communities from different socio-cultural backgrounds. The distinctive format of the Asmarakandi book also shows implications regarding its function as a learning resource for Islamic education. First, the used of the Asmarakandi book makes Islamic education take place systematically, effectively, and efficiently. Second, the suitability of the material with the level of religious understanding of the early Muslim community in the Nusantara. Third, the dialogue-based book format can encourage the critical power of the reviewers. Furthermore, fourth, the transformation of the book into local texts helps the general public understand the content of the Asmarakandi book.